Analisis Implementasi Prinsip-Prinsip Etika Bisnis Syariah pada Pedagang Pasar Alahan Panjang - Nurhamida Gusti; Yefri Joni (ARZUSIN, 2025)
Sharia business ethics represent a fundamental component of muamalah practices in Islam, emphasizing principles of honesty, justice, responsibility, and consumer care in commercial transactions. Although widely acknowledged within Islamic economic discourse, empirical studies specifically examining the implementation of these principles in local traditional markets—such as the Alahan Panjang Market—remain limited. This study aims to analyze the application of sharia business ethics in the trading practices of merchants at Alahan Panjang Market and to identify factors influencing adherence to these values. A qualitative field study approach was employed, involving merchants and consumers selected through purposive sampling. Data were collected via in-depth interviews, direct observation, and documentation, and analyzed through the stages of data reduction, data display, and interpretative conclusion drawing. The findings reveal that most merchants have implemented key ethical principles in their trading practices, particularly in transactional honesty, price fairness, accountability for merchandise, and consumer-oriented attitudes. However, inconsistencies persist, notably in aspects of price and quality transparency, influenced by economic competition, limited understanding of muamalah concepts, and insufficient oversight from market authorities and religious institutions. The study concludes that strengthening education on sharia business ethics, enhancing institutional supervision, and fostering collaboration between local governments and religious bodies are essential for guiding traditional market traders. This research contributes to the enrichment of Islamic business ethics literature in local contexts and offers practical implications for value-based trade policy development.